New aspect of allergic contact dermatitis, an inflammatory skin disorder mediated by mast cells: Can IL-38 help?. (June 2020) - Lauritano, Dorita; Ronconi, Gianpaolo; Caraffa, Alessandro; Enrica Gallenga, Carla; Kritas, Spyros K.; Di Emidio, Paolo; Martinotti, Stefano; Tetè, Giulia; Ross, Rhiannon; Conti, Pio
Abstract: Atopic dermatitis (AD) is an inflammatory reaction of the skin that can occur in several parts of the body and can be provoked or exacerbated by food and/or environmental compounds. Allergic contact dermatitis (ACD) is a potential enhancer of AD, and an epidermal barrier breaker which induces greater penetration of allergens and other compounds. ACD presents an eczematous rash, red and itchy, with inflammation mediated by cytokines. ACD is an immunological disorder caused by contact with an allergic substance (haptens) that involves immunotoxicity, irritation and inflammation. Mast cells (MCs) are important immune cells that intervene, as effector cells, in allergic and anaphylactic reactions, asthma, autoimmune diseases and cancer. In dermatitis, activated MCs release inflammatory chemical mediators and secrete pro-inflammatory cytokines, including interleukin (IL)-1, TNF, and IL-33. In addition, IL-1 activates MCs to generate a number of cytokines and chemokines, which aggravate inflammation. IL-38 cytokine, an IL-1 family member, is secreted by activated immune cells, including macrophages and lymphocytes, and possesses anti-inflammatory activity. IL-38, by binding IL-36 receptor (IL-36R), provokes suppression of inflammation in many immune diseases. In particular, IL-38 inhibits the generation of IL-1, IL-6 and IL-8 along with other cytokines/chemokines. Here, we hypothesize for the first time that IL-38 may suppresses the inflammatory response in dermatitis, exerting beneficial therapeutic effect.